Fenomena Pencemaran Limbah Minyak Hitam (Oil Spill) di Kabupaten Bintan ditinjau dari Perspektif Hukum Nasional - Risa Arviana; Putri Yanti; Heni Widiyani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Oil spill pollution always occurs in the waters of the Riau Islands, one of which is in the waters of Bintan Island. As a result of the oil spill pollution, several tourist areas were temporarily closed, which had an impact on the regional economy. This condition certainly threatens the ecology and also has an impact on the socio-economic impact of society. From several laws and regulations related to oil waste pollution in the sea, there are 3 important steps that are regulated, namely prevention/mitigation efforts, mitigation efforts, and recovery efforts. Furthermore, these preventive measures require improving facilities in the form of oil pollution detection equipment and ship equipment to prevent oil pollution. Institutional strengthening has also been regulated in law starting from strengthening local, regional, national and even international institutions to jointly take steps to prevent and control oil waste pollution in the sea.